Pedigree Analysis in Criollo Limonero - Villasmil Ontiveros, Yenen; Aranguren Méndez, José; Román, Rafael; Isea, William; Contreras, Gloria; Zambrano, Sunny; Jordana, Jordi (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
In order to continue the genetic program for the conservation of the Criollo Limonero population, a study was carried out to evaluate the genetic variability of this local breed. For this purpose, 2552 genealogical records from the Criollo herd at the Carrasquero Local Station (INIA) located at Playa Bonita, Mara County, North of Zulia State-Venezuela, during the 1985-2003 period were used. Global inbreedingÂ of the herd (fH) and animal inbreeding were determined; in addition, Average of relatedness (AR), probabilities of gene origin, number of founders (NF), effective number of founders (fe), effective ancestors number (fa), genome founders number (Ng ) and number of founders explaining 50% (F50) of the genetic variability. For the year 2003 fH was 0.35%, whereas AR, NF, fe, fa, Ng and F50 were 3.4%, 386, 63.5, 38, 27.71 and 18 respectively. Even though AR showed a high relationship among the individuals in the herd, fH did not have a significant increase. For this reason, mates should be planned carefully in order to avoid related mates. Probabilities of gene origin suggest that genetic variation has decreased in this population due to a bottleneck effect and genetic drift, without increasing inbreeding. An important genetic diversity exists in this population which should be preserved, given the importance of this genetic resource for the region and the country